2015
DOI: 10.3892/etm.2015.2669
|View full text |Cite
|
Sign up to set email alerts
|

Relief of diabetes by duodenal-jejunal bypass sleeve implantation in the high-fat diet and streptozotocin-induced diabetic rat model is associated with an increase in GLP-1 levels and the number of GLP-1-positive cells

Abstract: A recently invented duodenal-jejunal bypass sleeve (DJBS) implanted in the duodenum and proximal jejunum has exhibited good glycemic control in diabetes mellitus. However, the specific mechanism by which DJBS placement induces the remission of diabetes is not well known. Previous studies have indicated that changes in the pattern of gut hormone secretion may play a role. The aim of the present study was to explore the role of intestinal L cells and the production of glucagon-like peptide-1 (GLP-1) by these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Because of greatly reduced beta cell number and presumably decreased insulin levels, body weights of STZ rats did not increase throughout the experiment. Weight gain of STZ rats after RYGB was consistent with results of previous studies 25 and reflects amelioration of diabetes. The mechanism of weight gain in STZ rats undergoing RYGB may be due to increased pancreatic beta cell area 26 , reduced beta cell apoptosis 27 , increased beta cell proliferation 28 , and/or improved beta cell function 29 , as documented previously in rodents undergoing RYGB.…”
Section: Discussionsupporting
confidence: 90%
“…Because of greatly reduced beta cell number and presumably decreased insulin levels, body weights of STZ rats did not increase throughout the experiment. Weight gain of STZ rats after RYGB was consistent with results of previous studies 25 and reflects amelioration of diabetes. The mechanism of weight gain in STZ rats undergoing RYGB may be due to increased pancreatic beta cell area 26 , reduced beta cell apoptosis 27 , increased beta cell proliferation 28 , and/or improved beta cell function 29 , as documented previously in rodents undergoing RYGB.…”
Section: Discussionsupporting
confidence: 90%
“…Recent investigations have shown that the increased plasma GLP‐1 concentration in patients with type 2 diabetes who underwent a gastric bypass or sleeve gastrectomy surgery normalized their blood glucose levels. It has been reported that the possible mechanisms are that these surgeries lead to gut hypertrophy and an increase in the number of L cells in the LI, resulting in increased plasma GLP‐1 levels. However, these kinds of surgery are greatly invasive and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IGB therapy reduced plasma ghrelin levels (54) and increased levels of sirtuin-1 (55) (a well-known regulator of energy homeostasis and metabolism). Following DJBL implantation, increased fasting and postprandial glucagon-like peptide-1 (GLP-1) levels have been observed (34,56). GLP-1 can stimulate glucose-dependent insulin secretion, thereby reducing postprandial hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%